Morphological Assessment of Changes in the Macro- and Microvascular System of Lung Tissue in Diabetes Mellitus (Texas Journal of Medical Science, 2023)
Diabetes mellitus is a chronic metabolic disease that affects various organs, including the lungs. The morphological changes of the macro- and microvascular systems of lung tissue in diabetes mellitus remain largely unknown, which affects our understanding of the pathogenesis of diabetic lung diseases. This article aims to review recent research on morphological assessments of changes in the macro- and microvascular system of lung tissue in diabetes mellitus, with a focus on the available techniques and their limitations, as well as their potential applications in preventing and treating diabetic lung diseases.